2013
DOI: 10.3390/nu5072502
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Immune Function

Abstract: Vitamin D metabolizing enzymes and vitamin D receptors are present in many cell types including various immune cells such as antigen-presenting-cells, T cells, B cells and monocytes. In vitro data show that, in addition to modulating innate immune cells, vitamin D also promotes a more tolerogenic immunological status. In vivo data from animals and from human vitamin D supplementation studies have shown beneficial effects of vitamin D on immune function, in particular in the context of autoimmunity. In this rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
764
1
64

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 909 publications
(846 citation statements)
references
References 120 publications
(149 reference statements)
17
764
1
64
Order By: Relevance
“…The relation between vitamin D deficiency and Ss was shown in previous studies. [1][2][3][4] In our study, none of the patients had autoimmune disease such as Ss, which could affect the TBUT and Schirmer levels. We researched the possible link between non-Ss dry eye and vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relation between vitamin D deficiency and Ss was shown in previous studies. [1][2][3][4] In our study, none of the patients had autoimmune disease such as Ss, which could affect the TBUT and Schirmer levels. We researched the possible link between non-Ss dry eye and vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Vitamin D deficiency has an important role in the development of cancer and several autoimmune diseases. 1,2 It has also been found that environmental and hormonal factors, the fatsoluble vitamins such as vitamin D, may have a role in the pathogenic immunoregulatory process of primary Sjögren's syndrome (Pss). [4][5][6] The vitamin D supplementation is suggested for chronic autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D (1,25(OH) 2 D) thus synthesized may act directly on the receptor of vitamin D (VDR) [7] that is not only present in bones and intestines, but can also be found in bone marrow, brain, pancreas, prostate, and especially in tumor cells and immune cells, suggesting a much broader range of vitamin activity than simply calcium homeostasis [4,10].…”
Section: Source and Homeostasismentioning
confidence: 99%
“…The 1,25-dihydroxyvitamin D 3 (1,25(OH) 2 D 3 ) is the biologically active form of vitamin D. It is a pleiotropic hormone, regulating calcium and bone homeostasis due to its modulation of Ca 2+ ion absorption in the intestine [4]. It also regulates several genes, including those associated with the proliferation, differentiation, and apoptosis of cells [5].…”
Section: Source and Homeostasismentioning
confidence: 99%
“…Vitamin D plays several roles in the body, influencing bone health as well as serum calcium and phosphate levels. Furthermore, Vitamin D may modify immune function, cell proliferation, differentiation and apoptosis [1,2].…”
mentioning
confidence: 99%